Laparoscopic Surgery for Crohn Disease: A Brief Review of the Literature - Aarons, Cary B. (Clinics in Colon and Rectal Surgery, 2013)
Crohn disease remains a challenging clinical entity, both medically and surgically. It frequently presents in early adulthood and imposes a lifetime exposure to chronic inflammation that can affect the entire gastrointestinal tract. Although the mainstay of therapy is treatment with immunomodulating drugs, ∼70 to 90% of patients with Crohn disease will ultimately require surgery. Furthermore, there are high rates of symptomatic recurrences that may also require surgical intervention over time. There is no definitive cure for Crohn disease and surgery is reserved for failed medical therapy or the complications of the disease, namely, obstruction, septic complications (abscess, perforation), and fistulas. However, the robust inflammatory environment during these periods is not always conducive to a minimally invasive surgical approach. Despite the inherent technical challenges, the literature has increasingly shown that laparoscopy for Crohn disease, in the appropriate setting, is feasible and safe. In fact, it offers many advantages, which are particularly beneficial to this subset of patients, such as fewer wound complications, a shortened hospital course, less tissue trauma and subsequent adhesion formation, and earlier resumption of oral intake and bowel function.
Keywords: laparoscopy; Crohn disease; minimally invasive surgery